1970
DOI: 10.1149/1.2407297
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of the Zn-Cd-Te Ternary System

Abstract: The ternary Zn‐Cd‐Te liquidus surface and the pseudobinary CdTe‐ZnTe solidus curve have been determined by thermal analysis of cooling and heating curves, respectively, of homogenized liquid and solid alloy samples. The binary Cd‐Te and Zn‐Te liquidus arrest temperatures are in good agreement with most of the previously published data and confirm the presence of well‐ defined inflections on the metal‐rich and Te‐rich sides of both liquidus curves. The binary interchange energy parameters calculated along each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…(18) and rewriting (11), assuming the solid solution to be regular (i. e. I1Gxs = Wy(1-y)), we obtain the system for the ternary liquidus and solidus surfaces : [18]- [20]. We use the more recent work of'Steininger, Strauss and Brebrick [15] because it is supposed to be the most reliable and because it includes the study of the complete ternary system. The previously indicated works are in agreement for the metal-rich part of the liquidus of ZnTe and CdTe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(18) and rewriting (11), assuming the solid solution to be regular (i. e. I1Gxs = Wy(1-y)), we obtain the system for the ternary liquidus and solidus surfaces : [18]- [20]. We use the more recent work of'Steininger, Strauss and Brebrick [15] because it is supposed to be the most reliable and because it includes the study of the complete ternary system. The previously indicated works are in agreement for the metal-rich part of the liquidus of ZnTe and CdTe.…”
mentioning
confidence: 99%
“…(8) figure 11 is the estimated two-liquid region. However no experimental evidence of liquid immiscibility in the Zn-Te system has been found despite thorough re-investigations [15].…”
mentioning
confidence: 99%
“…The eutectic reaction temperature in the Cd-CdTe portion was reported by Kobayashi. 12 The melting temperature for CdTe was extensively measured by Kobayashi, 12 Lawson et al, 13 DeNobel, 14 Lorenz, 15 Steininger et al, 17 Mason and O'Kane, 20 Gromakov et al, 21 and Sysoev et al 22 The enthalpies of formation of CdTe were reported by Yamaguchi et al, 8 Lorenz, 15 Pool, 23 Robinson and Leach, 24 Agarwal et al, 25 McAteer and Seltz, 26 Shamsuddin and Nasar, 27 Brebrick and Strauss, 28 Robinson and Bever, 29 Rugg et al, 30 Amzil et al, 31 Terpilowski and Ratajzak, 32 Zabdyr, 33 Korneeva et al, 34 Goldfinger and Jeunehomme, 35 and Vanyukov et al 36 The enthalpies of mixing for the liquid phase were reported by Yamaguchi et al 8 and Amzil et al 31 The partial pressures of Cd (gas) and Te 2 (gas) in equilibrium with the liquid + CdTe two-phase mixtures at various temperatures were measured by DeNobel, 14 Lorenz, 15 Brebrick 18 and Shiozawa and Jost. 37 These data can be converted into the activities of Cd and Te in the liquid phase along the liquidus by the following equations:…”
Section: Literature Information the Cd-te Systemmentioning
confidence: 99%
“…While the segregation coefficient of zinc in (Cd,Zn)Te is as high as 1.35 [1], for (Cd,Mn)Te the segregation coefficient of manganese practically equals 1 [2], which means nearly no segregation of Mn. This is why the homogeneous Mn content can be obtained for larger size of the (Cd,Mn)Te plates, as compared with the (Cd,Zn)Te plates with homogeneous Zn content.…”
Section: Introductionmentioning
confidence: 96%